Analisis Strategi Pemasaran Digital dan Costumer Experience Terhadap Minat Beli Konsumen Pada wijaya engineering & Construction - Theysa Sahlani Pratiwi; Mutiara Praptasari; Siti Rugayah; Daz Vholasky Anggraini (LPPM Universitas Sains dan Teknologi Komputer, 2026)
CV. Wijaya Engineering & Construction is a company that focuses in the field of implementation and is also registered in Aksindo Association, CV. Wijaya Engineering & Construction is famous as, The implementation handled by CV. Wijaya Engineering & Construction is Construction Services, Concrete Works, Construction Services, Steel Works and Installation including Welding and Construction Services, Other Special Construction Works, Landscape or Gardening Works. This company was established on May 1, 2012, located in Rokan Hulu Regency, Pasir Pangaraian Riau, Various types of products and services in the Construction sector are marketed by CV. Wijaya Engineering & Construction In the process of marketing its products and services, this company carries out promotions by utilizing technological advances through digital media, either through websites or by joining the Indonesian Construction Contractor Association. The purpose of this study is to determine the Digital Marketing and Customer Experience strategies for Consumer Purchase Interest at CV. Wijaya Engineering & Construction. This research is a field research with a qualitative research type. Data collection techniques using interviews, and direct in-depth observations with customers. The results of the study are expected to provide practical recommendations to grow the interest of potential consumers, desire to strengthen the desire of potential consumers, and Customer Experience to increase customer loyalty by retargeting potential customers whose data has been entered due to paid advertising